Drivers of people's preferences for spatial proximity to energy infrastructure technologies: A cross-country analysis - Jason Harold; Valentin Bertsch; Thomas Lawrence; Magie Hall (The Economic and Social Research Institute (ESRI), 2018)
Many countries plan to decarbonise their energy systems by increasing energy efficiency and expanding the use of renewable energy sources (RES). Such actions require significant investments in new energy infrastructures. While people are generally accepting of these infrastructures, opposition sometimes arises when these developments are sited at close proximity to people's residences. Therefore, it is important to understand what actually drives people's preferences for spatial proximity to different energy infrastructure technologies. This study examines the factors influencing people's proximity preferences to different energy technologies using a cross-country econometric analysis of the stated preference data from an unprecedented survey conducted on nationally representative samples of the population in Ireland, the US and Germany. The survey involved more than 4,500 participants in total. This paper presents the data and selected results from a generalised ordered logit model for each energy technology surveyed. These are; wind turbines, solar power technology, biomass power plant, coal-red power plant and natural gas power plant. The results show that, in general, German and Irish citizens are willing to accept energy infrastructures at smaller distances to their homes than their US counterparts. Moreover, attitudinal factors are found to shape people's preferences more consistently than any of the socio-demographic characteristics.
Keywords: 330; spatial proximity; energy infrastructure technologies; people's preferences; cross-country analysis; local acceptance